The Aquatic Invertebrate Hydra vulgaris Releases Molecular Messages Through Extracellular Vesicles - Moros, Maria; Fergola, Eugenio; Marchesano, Valentina; Mutarelli, Margherita; Tommasini, Giuseppina; Miedziak, Beata; Palumbo, Giuliana; Ambrosone, Alfredo; Tino, Angela; Tortiglione, Claudia (Frontiers in Cell and Developmental Biology, 2021)
Recent body of evidence demonstrates that extracellular vesicles (EVs) represent the first language of cell-cell communication emerged during evolution. In aquatic environments, transferring signals between cells by EVs offer protection against degradation, allowing delivering of chemical information in high local concentrations to the target cells. The packaging of multiple signals, including those of hydrophobic nature, ensures target cells to receive the same EV-conveyed messages, and the coordination of a variety of physiological processes across cells of a single organisms, or at the population level, i.e. mediating the population´s response to changing environmental conditions. Here, we purified EVs from the medium of the freshwater invertebrate Hydra vulgaris, and the molecular profiling by proteomic and transcriptomic analyses revealed multiple markers of the exosome EV subtype, from structural proteins to stress induced messages promoting cell survival. Moreover, positive and negative regulators of the Wnt/β-catenin signaling pathway, the major developmental pathway acting in body axial patterning, were identified. Functional analysis on amputated polyps revealed EV ability to modulate both head and foot regeneration, suggesting bioactivity of the EV cargo and opening new perspectives on the mechanisms of developmental signalling. Our results open the path to unravel EV biogenesis and function in all cnidarian species, tracing back the origin of the cell-cell, cross-species or cross-kingdom communication in aquatic ecosystems